1987
DOI: 10.1136/hrt.58.3.254
|View full text |Cite
|
Sign up to set email alerts
|

Failure of propranolol to improve exercise tolerance in patients with mitral stenosis in sinus rhythm.

Abstract: SUMMARY Propranolol reduces left atrial pressure at rest and during exercise in patients with mitral stenosis by lowering cardiac output and heart rate. Ten patients (aged Propranolol did not improve objective or subjective exercise tolerance in patients with isolated mitral stenosis in sinus rhythm.The potential beneficial effect of, blockade in patients with mitral stenosis has been studied over the past 20 years.' -3 The rationale for these investigations was the understanding that the pressure gradient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Investigators who favor the use of (3-blockers in mitral stenosis generally report improved pulmonary capillary wedge pressure as a consequence of the beneficial action of P-antagonists [1,2,5,151. Although some investigators have suggested that ex- ercise performance is improved with P-antagonists [4,15], others have shown, in double-blind randomized placebo-controlled trials, no objective or subjective benefit in exercise performance [7]. Our results are similar to the results of Giuffrida et al [2], who reported that although propranolol reduced the gradient across the mitral valve during exercise, patients did not have an increase in exercise capacity.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Investigators who favor the use of (3-blockers in mitral stenosis generally report improved pulmonary capillary wedge pressure as a consequence of the beneficial action of P-antagonists [1,2,5,151. Although some investigators have suggested that ex- ercise performance is improved with P-antagonists [4,15], others have shown, in double-blind randomized placebo-controlled trials, no objective or subjective benefit in exercise performance [7]. Our results are similar to the results of Giuffrida et al [2], who reported that although propranolol reduced the gradient across the mitral valve during exercise, patients did not have an increase in exercise capacity.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, because stroke volume was little changed, the paradoxic effects of beta blocker therapy became apparent, since the benefit of reduced PCWP is offset by lost cardiac reserve ( 1 CO = 4 HR X -SV). These observations may explain the disparate finding in exercise response reported by others [4,7,15].…”
Section: Discussionmentioning
confidence: 82%
“…Contradictory results are reported on this subject from studies in the literature. [11][12][13][14][15] Cumming and Car 14 suggested that although beta blockers decrease the transmitral gradient, they also cause a decrease in cardiac performance in general and so they have no place in the treatment of MS. They related this to augmentation of left ventricular EDP by beta blockers by decreasing the cardiac output.…”
Section: Resultsmentioning
confidence: 99%